Characterization of hepatic steatosis using controlled attenuation parameter and MRI‐derived proton density fat fraction in living donor liver transplantation. Issue 11 (9th September 2022) - Zhuang, Rachel H.; Weinstock, Allison K.; Ganesh, Swaytha; Behari, Jaideep; Malik, Shahid M.; Bataller, Ramon; Furlan, Alessandro; Hughes, Christopher B.; Humar, Abhinav; Duarte‐Rojo, Andres
Abstract: Background: The increasingly favorable outcomes of live donor liver transplant warrant development of screening techniques to expand current donor pool. Transient elastography (TE) with controlled attenuation parameter (CAP) is accessible and has promising diagnostic performance in non‐obese individuals. Here, we demonstrate its utility in grading donor steatosis for risk assessment in living liver donors (LLD). Study Design: In a prospective study of LLD and recipients, accuracy was determined using MRI‐derived proton density fat fraction (PDFF) as reference. Results: One hundred and one LLD underwent TE, 95 of whom had available PDFF. Median CAP and MRI‐PDFF were 233 dB/m (206–270) and 2.9% (2.3–4.0), respectively. A CAP threshold of 270 dB/m captured all steatosis which was present in 13 (13%) LLD (AUROC .942, 100% sensitivity and 83% specificity). Performance further improved when excluding obese LLD and limiting analysis to M‐probe (AUROC .971 and .974, respectively, with 87% specificity). There was no difference in CAP and MRI‐PDFF between LLD and nondonors ( P  = .26 and .21, respectively). Early allograft dysfunction was observed in one recipient (CAP 316, PDFF 9.5%), zero underwent retransplant, and one died from sepsis. Conclusion: The specific role of CAP in living liver donation warrants further study, beginning with its use as screening tool across peripheral clinics.